The protective effect of sodium nitroprusside(SNP)treatment on Arabidopsis thaliana seedlings exposed to toxic level of Pb is not linked to avoidance of Pb uptake - Phang, Ing Chia; Leung, David W. M.; Taylor, H. Harry; Burritt, David J. (Academic Press, 2011)
The effects of 100 μM Pb(NO3)2 on 7-day-old Arabidopsis thaliana seedlings grown from seeds pretreated with a nitric oxide donor, sodium nitroprusside (SNP), or a nitric oxide scavenger, 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (cPTIO) were investigated. Physiological stress induced by Pb (reduced root growth) was less evident in seedlings grown from seeds pretreated with SNP. However, SNP pretreatment of seeds did not affect Pb accumulation in the seedlings. Pb exposure caused oxidative stress by elevating hydrogen peroxide (H2O2) and lipid hydroperoxide contents of the seedlings. SNP pretreatment of seeds counteracted Pb toxicity by reducing the H2O2 and lipid hydroperoxide contents of Pb-exposed seedlings. Additionally, Pb-induced rises in antioxidative enzyme activities were reversed by SNP pretreatment of seeds. It was concluded that the ameliorating effects of SNP pretreatment were associated with the release of nitric oxide because cPTIO reversed these effects of SNP pretreatment of seeds and more importantly SNP pretreatment did not trigger an avoidance mechanism.